Dynamic Analysis of Imperfect FGM Circular Cylindrical Shells Reinforced by FGM Stiffener System Using Third Order Shear Deformation Theory in Term of Displacement Components - Duc,Nguyen Dinh (2017)
Abstract This paper presents dynamic analysis of an eccentrically stiffened imperfect circular cylindrical shells made of functionally graded materials (FGM), subjected to axial compressive load and filled inside by elastic foundations in thermal environments by analytical method. Shells are reinforced by FGM stringers and rings taking into account thermal elements. The stability equations in terms of displacement components for stiffened shells are derived by using the third-order shear deformation theory and smeared stiffeners technique.The closed-form expressions for determining the natural frequency, nonlinear frequency-amplitude curve and nonlinear dynamic response are obtained by using Galerkin method and fourth-order Runge-Kutta method. The effects of stiffeners, foundations, imperfection, material and dimensional parameters pre-existent axial compressive and thermal load on dynamic responses of shells are considered.